Wyner-Ziv spatial scalable video coding using compressive sensing in ubiquitous networks - GAN Zong-liang; QI Li-na; TANG Gui-jin; ZHU Xiu-chang (Tongxin xuebao)
A novel Wyner-Ziv spatial scalable video coding using compressive sensing was proposed for the ubiquitous networks.At the encoder,both the base layer and enhancement layer encode the video signal independent,in which down-sampling video was coded by H.264 in the based layer and original video was coded with adaptive compressive sensing measurement,quantization and entropy coding in the enhancement layer.At the decoder,the base layer and enhancement layer jointly recovered the video signal using compressive sensing approach based on joint sparse model of inter frames.Theoretical analysis and experimental results show that the proposed video coding method can flexibly adjust the bit stream,and has better rate-distortion performance and the robustness of transmission.